THE RELATIONSHIP BETWEEN THE QUALITY OF SERVICE AND PATIENT SATISFACTION OF BPJS PARTICIPANTS IN THE RAUDHAH 2-7 INPATIENT ROOM OF DR. ZAINOEL ABIDIN BANDA ACEH GENERAL HOSPITAL IN 2023 - Prastama, Myranda; Agustina, Agustina; Hasnur, Hanifah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2025)
This study examines the relationship between the quality of health services and the satisfaction of BPJS patients in the Raudhah 2-7 inpatient ward at Dr. Zainoel Abidin General Hospital in 2023. A descriptive-analytic design with a cross-sectional approach was employed, involving 63 respondents selected through accidental sampling. Data was collected using questionnaires and interviews and analyzed using the Chi-Square test with SPSS version 22. The findings reveal a patient satisfaction rate of 69.8%, with significant associations between patient satisfaction and the dimensions of reliability (p = 0.000), responsiveness (p = 0.000), and empathy (p = 0.000). No significant associations were found with assurance (p = 0.076) and tangible aspects (p = 0.341). It is recommended that healthcare providers enhance service quality to improve patient comfort and satisfaction.